Teaching Video NeuroImage: Congenital Hemidystonia–Hemi-midbrain Atrophy Syndrome. (17th May 2022) - Pillai, Kanchana Soman; Thakre, Mahendra; Asole, Dnyaneshwar; Venkitachalam, Anil; Sundar, Uma; Sankhe, Ashwini P.; Joshi, Anagha R.; Firke, Vikrant P.
Abstract : An 18-year-old man with normal birth and development and a negative family history complained of nonprogressive clumsiness and posturing of his left hand since early childhood. His left limbs were shorter than his right but showed no evidence of atrophy (eFigure 1, A-C, links.lww.com/WNL/B902 ). Examination revealed dystonic posturing with mirror dystonia of the left hand and subtle mirror movements in his feet (Video 1). MRI of the brain showed right hemiatrophy of the midbrain, bilateral cortical activation with unilateral finger taps on fMRI, and normal corticospinal tract decussation (Figure, A-F). Levodopa response was present, suggesting dopaminergic denervation due to a congenital hemi-midbrain insult. 1 This case represents hemidystonia-hemiatrophy syndrome. 2 Subtle limb shortening and mirror dystonia can aid in diagnosis.